2015
DOI: 10.3892/mmr.2015.3157
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin ameliorates renal interstitial fibrosis via the inhibition of fibrocyte accumulation

Abstract: Abstract. Erythropoietin (EPO) is a hematopoietic hormone that protects against renal interstitial fibrosis in animal models; however, the mechanism underlying the anti-fibrotic activity of EPO has remained elusive. The present study aimed to elucidate this mechanism. Twenty-four male C57BL6 mice were randomly divided into four groups, each comprising six mice: i) control group (Sh); ii) unilateral ureteral obstruction (UUO) plus vehicle group (U+V); ⅲ) UUO plus 300 U/kg body weight recombinant human (rh)EPO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…[ 58 ] In response to injuries such as inflammation and hypoxia, the concentrations of chemokines in both peripheral blood and organs are elevated, and this elevation leads to accumulation of circulating fibrocytes in blood stream and injured organs. [ 59 60 ] This has been shown in many studies. For example, CXC-chemokine ligand 16 (CXCL16) (a transmembrane CXC chemokine) knockout mice administrated with angiotensin II (Ang II) were found to have significantly less circulating fibrocytes in injured kidney compared with these in wild-type mice,[ 61 ] indicating CXCL16 is one of the mediators involved in circulating fibrocyte recruitment.…”
Section: F Eatures Of C Irculating mentioning
confidence: 69%
“…[ 58 ] In response to injuries such as inflammation and hypoxia, the concentrations of chemokines in both peripheral blood and organs are elevated, and this elevation leads to accumulation of circulating fibrocytes in blood stream and injured organs. [ 59 60 ] This has been shown in many studies. For example, CXC-chemokine ligand 16 (CXCL16) (a transmembrane CXC chemokine) knockout mice administrated with angiotensin II (Ang II) were found to have significantly less circulating fibrocytes in injured kidney compared with these in wild-type mice,[ 61 ] indicating CXCL16 is one of the mediators involved in circulating fibrocyte recruitment.…”
Section: F Eatures Of C Irculating mentioning
confidence: 69%
“…A search of the literature shows that recombinant human erythropoietin and its synthetic derivatives (at least epoetin beta and methoxy polyethylene glycol-epoetin beta) have anti-oxidant, anti-inflammatory and cytoprotective properties [17,18,19,22,23,24,25]. But it cannot be concluded that different synthetic derivatives of epoetin may offer the same effects on cytoprotection, possibly a result that may reflect different affinities binding to the EPOR.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [24] reported that epoetin beta inhibits cardiac fibrosis in the experimental diabetes model. Recently, Geng et al [25] reported that epoetin ameliorates renal interstitial fibrosis in the experimental unilateral ureteral obstruction model. Furthermore, epoetin abrogated the unilateral ureteral obstruction induced increase in the number of bone marrow-derived myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, under pathologic conditions the resident renal fibroblasts transdifferentiate into myofibroblasts, which promote renal fibrosis by producing large amounts of extracellular matrix proteins rather than EPO (52). A study of mice showed that treatment with rhEPO significantly inhibited the accumulation of fibrocyte by inhibition of α-SMA upregulation, and thereby attenuating renal interstitial fibrosis (53). Another study of transgenic mice found that enhanced signaling mediated by hypoxia-inducible factor (HIF) in myofibroblast-transformed renal EPO-producing cells reactivated the synthesis of EPO, without influencing renal fibrosis or inflammation (54).…”
Section: Epo and Myofibroblastsmentioning
confidence: 99%